047 Trends in access site choice and PCI outcomes: insights from the UK national PCI dataset. (16th May 2012) - Ratib, K; Routledge, H; Mamas, M A; Lo, T; Fraser, D; Nolan, J
Abstract : Background: There has been a drive to change access site practice for PCI with the aim of reducing access site complications. This is increasingly important with the shift to more acute PCI with use of more potent antithrombotics. With the rapid uptake of transradial access in the UK we looked for changes in outcome using nationally collected data from the UK BCIS PCI dataset. Methods: Retrospective analysis of data submitted from all UK PCI centres between January 2006 and September 2011. Incomplete data and cases where multiple access sites were recorded were excluded. Results: Of 413 146 documented procedures a single access was recorded in 92.7%. The two cohorts, transradial and transfemoral were well matched for age. Transradial patients had less diabetes and fewer previous CABG but were more likely to be smokers, hypertensive, hyperlipidaemic and male. The use of transradial access increased from 17.2% in 2006 to 57% in 2011. Over this time PCI for ACS increased from 47% to 63% procedures, with the same increase in the proportion of transradial access. Primary PCI increased from 6% of all PCI to 25% in 2011. For femoral procedures mortality more than doubled (0.55% in 2006 to 1.36% in 2011) while for transradial procedures mortality only increased from 0.42% to 0.52%. When shock and IABP use are excluded the reduction in mortality for transradial PCI remains though the difference is reduced. Conclusion: The rapid change from femoral to radial access in the UK has been accompanied by a reduction in access site complications. As mortality and adverse outcomes have increased in keeping with patient and PCI complexity the rate of adverse outcomes in the patients treated radially has remained stable and lower than in the femoral group.